AZ-500 Microsoft Azure security technologies guided Cert prep - Warner, Tim; Diogenes, Yuri; Thomas, Orin 1973- (Pearson IT Certification, 2022)
AZ-500 Microsoft Azure Security Technologies Guided Cert Prep A complete path of videos, books, practice tests, and live training to help you gain exam readiness By: Tim Warner, Yuri Diogenes & Orin Thomas Level up your IT career with the knowledge required to become an AZ-500 Microsoft Azure Security Technologies expert. This expert-led certification study resource provides a guided path to exam success using video from the Complete Video Course series, Cert Guide chapters, and practice tests, including: Exam AZ-500 Microsoft Azure Security Technologies (Video) Exam Ref AZ-500 Microsoft Azure Security Technologies, Second Edition Pearson Practice Test: AZ-500 Microsoft Azure Security Engineer Associate Learners are also encouraged to supplement this training with live training: Exam AZ-500: Microsoft Azure Security Technologies Crash Course by Tim Warner This curated learning path unites video and book chapters so you can watch and read to learn and then quiz and test to prepare. With over 8 hours of video-based lessons, full deep-dive Pearson Cert Guide reading, and access to Pearson's test-prep practice tests this Guided Cert Prep has been designed to help you successfully prepare to take the AZ-500 Microsoft Azure Security Technologies exam. You'll learn in-demand associate-level skills concerning the knowledge of Microsoft Azure security which includes the tools and techniques for protecting identity, access, platforms, data, and applications to effectively manage security operations, and prepare for one of the most sought-after Microsoft certifications. A full range of topics on the AZ-500 Microsoft Azure Security Technologies exam are covered, including: Managing identity and access to Azure enforcing least-privilege security Implementing Azure platform protection Managing security operation in Azure environment Securing data and applications Featuring strategic, what-if scenarios to challenge and prepare for the exam Who should take this Guided Cert Prep Skill level Beginning to intermediate Certification candidates preparing for exam AZ-500 Microsoft Azure Security Technologies Any Microsoft certification candidate interested in learning the Azure Security Engineer skill set Any IT professional looking to understand how Microsoft Azure institutes information security This self-paced online training product requires an understanding of the basic Microsoft Azure security controls. It is recommended that candidates preparing for the Microsoft AZ-500 have at practical experience in administration of Azure and hybrid environments and experience with infrastructure as code, security operations processes, cloud capabilities, and Azure services. Guided Cert Prep includes 8 hours of targeted, video-based lessons led by industry experts Over 300 pages of deep-dive Cert Guide reading Self-study tools, such as in-book quizzes to self-assess your progress Access to the Pearson Test Prep practice exams to fully prepare for the AZ-500 exam Test-taking strategies to help you pass the AZ-500 exam with confidence.
Keywords: Windows Azure; Cloud computing -- Study guides -- Security measures -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Infonuagique; Sécurité; Mesures; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Study guides